Designing a QTL Mapping Study for Implementation in the Realized Collaborative Cross Genetic Reference Population. Issue 4 (16th October 2019) - Soller, Morris; Abu‐Toamih Atamni, Hanifa J.; Binenbaum, Ilona; Chatziioannou, Aristotelis; Iraqi, Fuad A.
Abstract: The Collaborative Cross (CC) mouse resource is a next‐generation mouse genetic reference population (GRP) designed for high‐resolution mapping of quantitative trait loci (QTL) of large effect affecting complex traits during health and disease. The CC resource consists of a set of 72 recombinant inbred lines (RILs) generated by reciprocal crossing of five classical and three wild‐derived mouse founder strains. Complex traits are controlled by variations within multiple genes and environmental factors, and their mutual interactions. These traits are observed at multiple levels of the animals' systems, including metabolism, body weight, immune profile, and susceptibility or resistance to the development and progress of infectious or chronic diseases. Herein, we present general guidelines for design of QTL mapping experiments using the CC resource—along with full step‐by‐step protocols and methods that were implemented in our lab for the phenotypic and genotypic characterization of the different CC lines—for mapping the genes underlying host response to infectious and chronic diseases. © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : CC lines for whole body mass index (BMI) Basic Protocol 2 : A detailed assessment of the power to detect effect sizes based on the number of lines used, and the number of replicates per line Basic Protocol 3 : Obtaining power for QTL with given target effect by interpolating in Table 1 of Keele et al. (2019)